Precast concrete systems in developing vs. industrialized countries - Polat, Gul (Journal of Civil Engineering and Management, 2010)
Precast concrete technology is recognized worldwide as offering significant advantages. Despite the advantages they offer, precast concrete building systems’ share in both Turkey and the U.S. is very low, especially when compared to many European countries. Since Turkey is a developing country that is technologically dependent on the developed world, low share of industrialized building systems is highly expected in that country. However, the U.S. is a developed and industrialized country, so it was very interesting to see that these systems are not extensively used in that country either. This study investigated the factors that prevent the extensive use of precast concrete systems in the U.S. and Turkey through an extensive questionnaire survey. The survey results revealed that the perceptions of the American vs. Turkish respondents on most of the factors that affect the use of precast concrete systems are significantly different from each other. While American respondents considered size and load restrictions on transportation, poor communication among parties, and lack of qualified contractors specialized in precast concrete systems as three most important barriers to the extensive use of precast concrete systems in the U.S. building construction market, Turkish respondents ranked lack of good communication among parties and lack of structural engineers and contractors specialized in precast concrete systems as the most important three factors that prevent the extensive use of these systems in Turkey. This study indicated that precast concrete users and manufacturers should recognize that the main reasons for low utilization of precast concrete systems predominantly depend on the prevailing conditions of the country in question.Published Published Online: 14 Oct 2010